Moisture-absorbing and sweat-stain-preventing fabric and preparation method thereof
By modifying PET and inorganic fillers, the performance of polyethylene terephthalate is enhanced, and combined with hydrochloric acid solution and antibacterial moisture absorption finishing agents are solved, and the fabric's moisture absorption quick-drying performance, antibacterial and water-resistant performance are insufficient, achieving multiple performance improvements of the fabric.
Patent Information
- Application Number
- CN202411682252.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing clothing fabrics have shortcomings in moisture absorption and quick-drying performance, antibacterial and odor resistance and water-resistant properties, especially after washing, these properties will drop rapidly.
Compound PET fibers are prepared by mixing polyethylene terephthalate, modified PET, inorganic filler and additives, and then melt extrusion and spinning, and then so as to make hydrochloric acid solution impregnation and antibacterial moisture absorption finishing agent, so as to improve the moisture absorption and rapid drying performance of the fabric and improve its water washing resistance.
It significantly improves the moisture-absorbing and sweat-resistant fabric's moisture-absorbing and sweat-resistant properties, ensuring that the fabric can maintain good performance after multiple washes.
Smart Images

Figure BDA0005148641450000031 
Figure BDA0005148641450000051 
Figure BDA0005148641450000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of moisture-absorbing fabric processing, and in particular to a moisture-absorbing and sweat-proof fabric and a preparation method thereof. Background Art
[0002] Today, with the rapid development of textile technology, the research and development of functional fabrics has become an important force in promoting the progress of the textile industry. Especially in the pursuit of quality of life and health, consumers' functional demands for clothing fabrics are becoming increasingly diversified, among which moisture absorption, anti-perspiration and other functions are particularly concerned. This type of fabric can not only effectively improve the comfort of wearing, but also keep the body dry and clean in specific environments, avoiding unnecessary embarrassment and discomfort.
[0003] In the prior art, a Chinese invention patent with publication number CN114059218A discloses a new type of sweat-proof fabric, including a surface waterproof layer and a close-fitting moisture-absorbing and breathable layer. The surface waterproof layer is woven from waterproof yarn made of a blend of polyester fiber and cotton fiber, and the close-fitting moisture-absorbing and breathable layer is woven from moisture-absorbing and breathable yarn made of a blend of polyester fiber, bamboo fiber and Tencel fiber. It has excellent moisture absorption performance, can quickly and massively absorb sweat from the human body surface, eliminate sweat, and enhance the human body's comfort.
[0004] The above content is to modify the fabric through multiple fibers to improve the moisture absorption and breathability of the fabric, so that the fabric will not form obvious color difference on the fabric after absorbing sweat. However, for the color difference problem of the fabric after it is wet, the color difference caused by absorbing water can be reduced by changing the color of the fabric. The impact of sweat stains is more about the odor caused by the fermentation of bacteria in the sweat stains after the fabric absorbs sweat and the wet skin-sticking effect of the clothing fabric after absorbing sweat.
[0005] However, most clothing fabrics are modified with antibacterial finishing agents, which have limited improvement on the fabrics' moisture absorption and quick-drying properties and antibacterial and anti-odor properties. In addition, after washing, the antibacterial properties and moisture absorption and quick-drying properties will decrease rapidly, and the wash resistance needs to be further improved.
[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0007] The object of the present invention is to provide a moisture-absorbing and sweat-proof fabric and a preparation method thereof, so as to solve the technical problem in the prior art that the moisture-absorbing and quick-drying performance, antibacterial and anti-odor performance and water-washing resistance of clothing fabrics need to be further improved.
[0008] The purpose of the present invention can be achieved by the following technical scheme: A method for preparing a moisture-absorbing and sweat-proof fabric comprises the following steps:
[0009] S1, polyethylene terephthalate, modified PET, inorganic filler and additive are mixed evenly and added into a twin-screw extruder, melt-extruded into a melt spinning machine, and melt-spinned to obtain a composite PET fiber crude product;
[0010] S2, adding the crude composite PET fiber and the hydrochloric acid solution into a beaker to keep them completely immersed, raising the temperature of the beaker to 70-80° C., and heat-treating for 2-3 hours, and post-treating to obtain the composite PET fiber;
[0011] S3, plying and twisting the composite PET fibers to prepare a mixed yarn with a linear density of 77-82 dtex, and then preparing a moisture-absorbing and sweat-proof fabric blank by weaving a plain weave;
[0012] S4. Using an antibacterial moisture-absorbing finishing agent to perform padding finishing on the moisture-absorbing and sweat-proof fabric blank to obtain the moisture-absorbing and sweat-proof fabric.
[0013] Furthermore, in step S1, the weight ratio of the polyethylene terephthalate, modified PET, inorganic filler and additive is 80-100:55-65:2-3:0.8-1, the additive is composed of a dispersant, a plasticizer and an antioxidant in a weight ratio of 2:3:1, the dispersant is a stearate, the plasticizer is a phthalate, the antioxidant is one or more of antioxidant A, antioxidant D, and antioxidant H, the inorganic filler is composed of nano titanium dioxide and zinc chloride in a weight ratio of 1:1, the temperatures of the six temperature sections of the twin-screw extruder from the feed end to the discharge end are 260°C, 270°C, 280°C, 280°C, 280°C, and 280°C, respectively, the spindle speed of the twin-screw extruder is 18-22rpm, and the spinning temperature of the melt spinning machine is 285-295°C.
[0014] Furthermore, in step S2, the usage ratio of the crude composite PET fiber and the hydrochloric acid solution is 1g:10mL, the concentration of the hydrochloric acid solution is 0.1-0.3mol / L, and the post-treatment includes: after the reaction is completed, the temperature of the beaker is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, the filter cake is transferred to an oven at a temperature of 60-70°C, and dried to constant weight to obtain a composite PET fiber.
[0015] Furthermore, in step S3, the warp yarn density of the moisture-absorbing and sweat-proof fabric blank is 140-170 yarns / inch, and the weft yarn density is 90-130 yarns / inch.
[0016] Further, the modified PET is processed by the following steps:
[0017] A1. Add sodium 5-sulfoisophthalate dimethyl ester, ethylene glycol and a catalyst into a four-necked flask and stir. The temperature of the four-necked flask is raised to 190-200° C. and stirred for 6-8 hours. After post-treatment, sodium 5-sulfoisophthalate diethylene glycol ester is obtained.
[0018] The synthetic reaction formula of diethylene glycol isophthalate-5-sodium sulfonate is:
[0019]
[0020] The synthetic reaction principle of diethylene glycol 5-sodium sulfoisophthalate is as follows:
[0021] Under high temperature and catalyst conditions, the methyl ester group on the sodium dimethyl isophthalate-5-sulfonate molecule undergoes an ester exchange reaction with the hydroxyl group on the ethylene glycol molecule, forming hydroxyl modifications at both ends of the sodium dimethyl isophthalate-5-sulfonate to prepare sodium diethylene glycol isophthalate-5-sulfonate and by-product methanol. The mass spectrometry analysis data of the sodium diethylene glycol isophthalate-5-sulfonate are m / z: 356.0178 (100.0%), 357.0212 (13.0%), 358.0136 (4.5%), and 358.0220 (1.8%).
[0022] A2. Add dihydroxyethyl terephthalate, sodium diethylene glycol 5-sulfonate isophthalate, terephthalic acid, polyethylene glycol 400, ethylene glycol and a catalyst into a nitrogen-protected four-necked flask and stir. The temperature of the four-necked flask is raised to 240-260° C., the pressure of the four-necked flask is reduced to 80-100 Pa, and the reaction is kept warm for 5-7 hours. The modified PET is obtained by post-treatment.
[0023] The synthetic reaction mechanism of modified PET is:
[0024] Under the action of high temperature and catalyst, the carboxyl groups of bis(hydroxyethyl) terephthalate, sodium diethylene glycol 5-sulfonate and terephthalic acid undergo esterification reaction with the hydroxyl groups of polyethylene glycol, ethylene glycol or bis(hydroxyethyl) terephthalate to generate polyester chains, accompanied by the generation and removal of water. As the esterification reaction proceeds, the generated polyester chains gradually grow and enter the polycondensation stage. The hydroxyl groups and ester groups between the polyester chains may further undergo polycondensation reaction to form polyester with a higher molecular weight, thereby preparing modified PET.
[0025] Furthermore, in step A1, the weight ratio of dimethyl isophthalate-5-sodium sulfonate, ethylene glycol and the catalyst is 3:1:0.01, and the post-treatment includes: after the reaction is completed, ethylene glycol is distilled off under reduced pressure to obtain diethylene glycol isophthalate-5-sodium sulfonate; in step A2, the weight ratio of bis(hydroxyethyl) terephthalate, dimethyl isophthalate-5-sodium sulfonate, terephthalic acid, polyethylene glycol 400, ethylene glycol 62.1 and the catalyst is 25:29:33:40:20:1, the catalyst is zinc acetate, and the post-treatment includes: after the reaction is completed, discharging while hot, curing after cooling to room temperature, and crushing to obtain modified PET.
[0026] Furthermore, the antibacterial moisture absorbing finishing agent is obtained by processing the following steps:
[0027] B1, adding modified allylamine, fumaric acid and deionized water into a four-necked flask protected by nitrogen and stirring, raising the temperature of the four-necked flask to 75-85°C, dropping the initiator solution into the four-necked flask, keeping the temperature for reaction for 6-8h, and post-treating to obtain composite polyallylamine;
[0028] The synthetic reaction formula of composite polyallylamine is:
[0029]
[0030] The synthetic reaction mechanism of composite polyallylamine is:
[0031] Under the action of the initiator, the olefin double bonds on the modified allylamine and fumaric acid molecules are opened to form double-terminal free radicals, and free radical polymerization occurs to form long-chain modified polyolefins with carboxyl, sulfonic acid and quaternary ammonium salt to obtain composite polyallylamine.
[0032] B2. Add the composite polyallylamine and deionized water into a beaker and stir until the system is dissolved. Add the catalyst into the beaker and stir until the system is dissolved. Stir for 10-20 minutes and adjust the pH of the system to 4-5 to obtain an antibacterial hygroscopic finishing agent.
[0033] Furthermore, in step B1, the modified allylamine, fumaric acid, deionized water and initiator solution are used in a ratio of 5g:2g:30mL:1.5g, and the initiator solution is composed of potassium persulfate and deionized water in a ratio of 1g:5mL. The post-treatment includes: after the reaction is completed, the solvent is evaporated under reduced pressure, tetrahydrofuran is added to a four-necked flask and stirred until the system is dissolved, cyclohexane is added to the four-necked flask, stirred for 10-20min, filtered, the filter cake is washed with cyclohexane twice and then dried, and the filter cake is transferred to a drying oven at a temperature of 50-60°C, and vacuum dried to constant weight to obtain a composite polyallylamine; in step B2, the composite polyallylamine, deionized water and catalyst are used in a ratio of 10g:40-50mL:0.3-0.5g, and the catalyst is sodium hypophosphite monohydrate.
[0034] Furthermore, the preparation method of the modified allylamine is: add dimethylallylamine and tetrahydrofuran into a four-necked flask protected by nitrogen and stir, increase the temperature of the four-necked flask to 50-60°C, dropwise add 1,3-propane sultone solution into the four-necked flask, and after the dropwise addition is completed, heat and react for 6-7 hours, and post-treat to obtain the modified allylamine.
[0035] The synthetic reaction formula of modified allylamine is:
[0036]
[0037] The synthetic reaction mechanism of modified allylamine is:
[0038] Under heating and stirring conditions, 1,3-propane sultone undergoes a ring-opening reaction in a mixed solution of dimethylallylamine and tetrahydrofuran to generate a quaternary ammonium salt modified with a sulfonic acid group to obtain modified allylamine. The hydrogen spectrum data of the modified allylamine are: 1H-NMR (D2O): 5.96 (1H), 5.66 (2H), 3.86 (2H), 3.35 (2H), 3.00 (6H), 2.88 (2H), 2.14 (2H).
[0039] Furthermore, the dosage ratio of the dimethylallylamine and 1,3-propane sultone is 1 mol:1.1 mol, the dosage ratio of the dimethylallylamine and tetrahydrofuran is 1 g:3-5 mL, the 1,3-propane sultone solution is composed of 1,3-propane sultone and tetrahydrofuran in a dosage ratio of 1 g:3 mL, and the post-treatment comprises: after the reaction is completed, distilling off the solvent under reduced pressure to obtain modified allylamine.
[0040] Furthermore, in step S4, the padding finishing method is: immersing the hygroscopic and sweat-proof fabric blank into an antibacterial hygroscopic finishing agent at a temperature of 50-60°C, keeping it warm and soaking it for 60-80 minutes, taking the hygroscopic and sweat-proof fabric blank out of the antibacterial finishing agent, draining it, obtaining a wet fabric with a water content of 55-65wt%, baking and drying it, and obtaining a hygroscopic and sweat-proof fabric.
[0041] Furthermore, the bath ratio of the moisture-absorbing and sweat-proof fabric blank and the antibacterial moisture-absorbing finishing agent is 1g:25-35mL, and the baking and drying operation includes: placing the wet fabric in an oven at a temperature of 70-80°C, baking for 8-10min, increasing the oven temperature to 160-180°C at a heating rate of 3-5°C / min, keeping warm and baking for 3-5min, naturally cooling to room temperature, washing with drinking water 3 times, and drying to obtain the moisture-absorbing and sweat-proof fabric.
[0042] The invention also provides a moisture-absorbing and sweat-proof fabric, which is obtained by adopting the preparation method of the moisture-absorbing and sweat-proof fabric.
[0043] The present invention has the following beneficial effects:
[0044] 1. The moisture-absorbing and sweat-proof fabric of the present invention is characterized in that sulfonate and polyethylene glycol segments are introduced into modified PET molecular segments to improve the moisture absorption and softness of the modified PET, and polyethylene terephthalate is reinforced and modified with modified PET and inorganic fillers to improve the moisture absorption and softness of the composite PET fiber, and then hydrochloric acid is used as an eluent to elute the zinc chloride nodes embedded in the composite PET fiber crude product to form a composite PET fiber with a porous structure, thereby increasing the porosity of the composite PET fiber, providing more channels for the transfer of moisture and water, making it easier for moisture and water to be transferred through these gaps, thereby improving the transfer efficiency, reducing the resistance that moisture or water may encounter during the transfer process, and improving the moisture absorption and quick-drying performance of the fabric. Nano titanium dioxide, as a photocatalytic material, can produce an antibacterial effect under ultraviolet light irradiation, and achieves the purpose of sterilization by destroying the cell wall or cell membrane of bacteria, thereby improving the antibacterial performance of the composite PET fiber.
[0045] 2. The hygroscopic and sweat-proof fabric of the present invention is prepared by preparing a composite polyallylamine having carboxyl, sulfonic acid and quaternary ammonium salt long-chain modified polyolefin, a large number of carboxyl groups and quaternary ammonium salts modified on the composite polyallylamine molecules have good hydrophilicity, and the carboxyl groups on the composite allylamine molecules react with the carboxyl groups or amino groups on the surface of the hygroscopic and sweat-proof fabric blank under the condition of a catalyst to form a covalent bond, thereby fixing the composite polyallylamine on the surface of the hygroscopic and sweat-proof fabric blank to prevent the composite polyallylamine from falling off during the washing process. Improve its wash resistance. The hydrophilic groups in the antibacterial moisture-absorbing finishing agent not only help the fabric absorb moisture, but also accelerate the transfer of moisture through the channels and gaps inside the fiber. When the fabric absorbs moisture, the moisture can be quickly transferred to the outer surface of the fabric through the channels inside the fiber, thereby accelerating the drying speed of the fabric, further improving the moisture absorption and quick-drying performance of the moisture-absorbing and sweat-proof fabric, and the quaternary ammonium salt modified on the composite polyallylamine, the quaternary ammonium salt and titanium dioxide cooperate with each other to further improve the antibacterial properties of the moisture-absorbing and sweat-proof fabric. DETAILED DESCRIPTION
[0046] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] Example 1
[0048] This embodiment provides a method for preparing a moisture-absorbing and sweat-proof fabric, comprising the following steps:
[0049] S1. Preparation of modified PET
[0050] Weigh: 300 g of sodium dimethyl 5-sulfonate, 100 g of ethylene glycol and 1 g of zinc acetate, add them into a four-necked flask and stir, raise the temperature of the four-necked flask to 190° C., keep stirring for 6 hours, and evaporate the unreacted ethylene glycol under reduced pressure to obtain sodium diethylene glycol 5-sulfonate.
[0051] Weigh: 250g of dihydroxyethyl terephthalate, 290g of sodium diethylene glycol 5-sulfonate isophthalate, 330g of terephthalic acid, 400400g of polyethylene glycol, 200g of ethylene glycol and 10g of zinc acetate, add into a four-necked flask protected by nitrogen and stir, raise the temperature of the four-necked flask to 240°C, reduce the pressure of the four-necked flask to 80Pa, keep the temperature and react for 5h, discharge the material while hot, cool to room temperature and solidify, and crush to obtain modified PET.
[0052] S2. Preparation of composite PET fibers
[0053] The nano titanium dioxide and nano zinc chloride are mixed uniformly in a weight ratio of 1:1 to obtain an inorganic filler;
[0054] Mix sodium stearate, diisononyl phthalate and antioxidant A in a weight ratio of 2:3:1 to obtain an additive;
[0055] Weigh: 800 g of polyethylene terephthalate, 550 g of modified PET, 20 g of inorganic filler and 8 g of additive, mix them evenly, add them into a twin-screw extruder, melt-extrude them into a melt spinning machine, and melt-spin to obtain a crude composite PET fiber, wherein the temperatures of the six temperature sections of the twin-screw extruder from the feed end to the discharge end are 260° C., 270° C., 280° C., 280° C., 280° C., 280° C., 280° C., respectively, the main shaft speed of the twin-screw extruder is 18 rpm, and the spinning temperature of the melt spinning machine is 285° C.;
[0056] The crude composite PET fiber and 0.1 mol / L hydrochloric acid solution were added to a beaker at a dosage ratio of 1 g:10 mL to keep them completely immersed. The temperature of the beaker was raised to 70°C and kept warm for 2 hours. The temperature of the beaker was lowered to room temperature and filtered. The filter cake was washed with purified water until it was neutral and then dried. The filter cake was transferred to an oven at 60°C and dried to constant weight to obtain a composite PET fiber.
[0057] S3. Preparation of moisture-absorbing and sweat-proof fabric blanks
[0058] The composite PET fibers were twisted and plied to prepare a mixed yarn with a linear density of 77 dtex, which was then plain woven to obtain a moisture-absorbing and sweat-proof fabric blank with a warp density of 140 yarns / inch and a weft density of 90 yarns / inch.
[0059] S4. Preparation of antibacterial moisture absorbing finishing agent
[0060] Weigh: 134.4 g of 1,3-propane sultone and 403.2 mL of tetrahydrofuran, mix well to obtain a 1,3-propane sultone solution for later use;
[0061] Weigh: 85.2 g of dimethylallylamine and 255.6 mL of tetrahydrofuran are added to a four-necked flask protected by nitrogen and stirred. The temperature of the four-necked flask is raised to 50° C. The 1,3-propane sultone solution prepared above is added dropwise to the four-necked flask. After the addition is complete, the mixture is kept warm for 6 hours and the solvent is evaporated under reduced pressure to obtain modified allylamine;
[0062] Potassium persulfate and deionized water were mixed evenly at a ratio of 1 g:5 mL to obtain an initiator solution;
[0063] Weigh: 100 g of modified allylamine, 40 g of fumaric acid and 600 mL of deionized water are added to a four-necked flask protected by nitrogen and stirred. The temperature of the four-necked flask is raised to 75°C. 30 g of the initiator solution is added dropwise to the four-necked flask. The mixture is kept warm for 6 hours. The solvent is evaporated under reduced pressure. 300 mL of tetrahydrofuran is added to the four-necked flask and stirred until the system is dissolved. 3000 mL of cyclohexane is added to the four-necked flask and stirred for 10 minutes. The filter cake is washed twice with cyclohexane and then dried. The filter cake is transferred to a drying oven at 50°C and vacuum dried to constant weight to obtain a composite polyallylamine.
[0064] Weigh: 100 g of composite polyallylamine and 400 mL of deionized water are added to a beaker and stirred until the system is dissolved, 3 g of sodium hypophosphite monohydrate is added to the beaker and stirred until the system is dissolved, and hydrochloric acid is added to the beaker to adjust the pH of the system to 4 to obtain an antibacterial hygroscopic finishing agent.
[0065] S5. Preparation of moisture-absorbing and sweat-proof fabric
[0066] According to the bath ratio of 1g:25mL, the hygroscopic and anti-perspiration fabric blank is immersed in the antibacterial hygroscopic finishing agent at a temperature of 50°C, and the temperature is kept for 60 minutes, and then the hygroscopic and anti-perspiration fabric blank is taken out from the antibacterial finishing agent, and drained to obtain a wet fabric with a water content of 55wt%;
[0067] The wet fabric was placed in an oven at 70°C and baked for 8 minutes. The oven temperature was increased to 160°C at a heating rate of 3°C / min, and the fabric was kept warm and baked for 3 minutes. The fabric was naturally cooled to room temperature, washed 3 times with drinking water, and dried to obtain a moisture-absorbing and sweat-proof fabric.
[0068] Example 2
[0069] This embodiment provides a method for preparing a moisture-absorbing and sweat-proof fabric, comprising the following steps:
[0070] S1. Preparation of modified PET
[0071] Weigh: 300 g of sodium dimethyl 5-sulfonate, 100 g of ethylene glycol and 1 g of zinc acetate, add into a four-necked flask and stir, raise the temperature of the four-necked flask to 195° C., keep stirring for 7 h, and evaporate the unreacted ethylene glycol under reduced pressure to obtain sodium diethylene glycol 5-sulfonate.
[0072] Weigh: 250g of dihydroxyethyl terephthalate, 290g of sodium diethylene glycol 5-sulfonate isophthalate, 330g of terephthalic acid, 400400g of polyethylene glycol, 200g of ethylene glycol and 10g of zinc acetate, add into a four-necked flask protected by nitrogen and stir, raise the temperature of the four-necked flask to 250°C, reduce the pressure of the four-necked flask to 90Pa, keep the reaction warm for 6h, discharge the material while hot, solidify after cooling to room temperature, and crush to obtain modified PET.
[0073] S2. Preparation of composite PET fibers
[0074] The nano titanium dioxide and zinc chloride are mixed uniformly in a weight ratio of 1:1 to obtain an inorganic filler;
[0075] Calcium stearate, diisodecyl phthalate and antioxidant D are uniformly mixed in a weight ratio of 2:3:1 to obtain an additive;
[0076] Weigh: 900 g of polyethylene terephthalate, 600 g of modified PET, 25 g of inorganic filler and 9 g of additive, mix well and add into a twin-screw extruder, melt extrude into a melt spinning machine, melt spin to obtain a composite PET fiber crude product, wherein the temperatures of the six temperature sections from the feed end to the discharge end of the twin-screw extruder are 260° C., 270° C., 280° C., 280° C., 280° C., 280° C., 280° C., the main shaft speed of the twin-screw extruder is 20 rpm, and the spinning temperature of the melt spinning machine is 290° C.;
[0077] The crude composite PET fiber and 0.2 mol / L hydrochloric acid solution were added to a beaker at a dosage ratio of 1 g:10 mL to keep them completely immersed. The temperature of the beaker was raised to 75°C and kept warm for 2.5 hours. The temperature of the beaker was lowered to room temperature and filtered. The filter cake was washed with purified water until it was neutral and then dried. The filter cake was transferred to an oven at 65°C and dried to constant weight to obtain the composite PET fiber.
[0078] S3. Preparation of moisture-absorbing and sweat-proof fabric blanks
[0079] The composite PET fibers were twisted and plied to prepare a mixed yarn with a linear density of 80 dtex, which was then plain woven to obtain a moisture-absorbing and sweat-proof fabric blank with a warp density of 155 yarns / inch and a weft density of 110 yarns / inch.
[0080] S4. Preparation of antibacterial moisture absorbing finishing agent
[0081] Weigh: 134.4 g of 1,3-propane sultone and 403.2 mL of tetrahydrofuran, mix well to obtain a 1,3-propane sultone solution for later use;
[0082] Weigh: 85.2 g of dimethylallylamine and 340.8 mL of tetrahydrofuran are added to a four-necked flask protected by nitrogen and stirred. The temperature of the four-necked flask is raised to 55° C. The 1,3-propane sultone solution prepared above is added dropwise to the four-necked flask. After the addition is complete, the mixture is kept warm for 6.5 h and the solvent is evaporated under reduced pressure to obtain modified allylamine;
[0083] Potassium persulfate and deionized water were mixed evenly at a ratio of 1 g:5 mL to obtain an initiator solution;
[0084] Weigh: 100 g of modified allylamine, 40 g of fumaric acid and 600 mL of deionized water are added to a four-necked flask protected by nitrogen and stirred. The temperature of the four-necked flask is raised to 80°C. 30 g of the initiator solution is added dropwise to the four-necked flask. The mixture is kept warm for 7 hours. The solvent is evaporated under reduced pressure. 300 mL of tetrahydrofuran is added to the four-necked flask and stirred until the system is dissolved. 3000 mL of cyclohexane is added to the four-necked flask and stirred for 15 minutes. The filter cake is washed twice with cyclohexane and then dried. The filter cake is transferred to a drying oven at a temperature of 55°C and vacuum dried to constant weight to obtain a composite polyallylamine.
[0085] Weigh: 100 g of composite polyallylamine and 450 mL of deionized water are added to a beaker and stirred until the system is dissolved, 4 g of sodium hypophosphite monohydrate is added to the beaker and stirred until the system is dissolved, and hydrochloric acid is added to the beaker to adjust the pH of the system to 4.5 to obtain an antibacterial hygroscopic finishing agent.
[0086] S5. Preparation of moisture-absorbing and sweat-proof fabric
[0087] According to the bath ratio of 1g:30mL, the hygroscopic and anti-perspiration fabric blank is immersed in the antibacterial hygroscopic finishing agent at a temperature of 55°C, and the temperature is kept and immersed for 70 minutes, and then the hygroscopic and anti-perspiration fabric blank is taken out from the antibacterial finishing agent, and drained to obtain a wet fabric with a water content of 60wt%;
[0088] The wet fabric was placed in an oven at 75°C and baked for 9 minutes. The oven temperature was increased to 170°C at a heating rate of 4°C / min, and the fabric was kept warm and baked for 4 minutes. The fabric was naturally cooled to room temperature, washed three times with drinking water, and dried to obtain a moisture-absorbing and sweat-proof fabric.
[0089] Example 3
[0090] This embodiment provides a method for preparing a moisture-absorbing and sweat-proof fabric, comprising the following steps:
[0091] S1. Preparation of modified PET
[0092] Weigh: 300 g of sodium dimethyl 5-sulfonate isophthalate, 100 g of ethylene glycol and 1 g of zinc acetate, add them into a four-necked flask and stir, raise the temperature of the four-necked flask to 200° C., keep stirring for 8 hours, and evaporate the unreacted ethylene glycol under reduced pressure to obtain sodium diethylene glycol 5-sulfonate isophthalate.
[0093] Weigh: 250g of dihydroxyethyl terephthalate, 290g of sodium diethylene glycol 5-sulfonate isophthalate, 330g of terephthalic acid, 400400g of polyethylene glycol, 200g of ethylene glycol and 10g of zinc acetate, add into a four-necked flask protected by nitrogen and stir, raise the temperature of the four-necked flask to 260°C, reduce the pressure of the four-necked flask to 100Pa, keep warm and react for 7h, discharge while hot, cool to room temperature and solidify, crush to obtain modified PET.
[0094] S2. Preparation of composite PET fibers
[0095] The nano titanium dioxide and zinc chloride are mixed uniformly in a weight ratio of 1:1 to obtain an inorganic filler;
[0096] Mix zinc stearate, di-n-octyl phthalate and antioxidant H in a weight ratio of 2:3:1 to obtain an additive;
[0097] Weigh: 1000g of polyethylene terephthalate, 650g of modified PET, 30g of inorganic filler and 10g of additive, mix them evenly and add them into a twin-screw extruder, melt-extrude them into a melt spinning machine, and melt-spin to obtain a crude composite PET fiber, wherein the temperatures of the six temperature sections of the twin-screw extruder from the feed end to the discharge end are 260°C, 270°C, 280°C, 280°C, 280°C, 280°C, 280°C, respectively, the main shaft speed of the twin-screw extruder is 22rpm, and the spinning temperature of the melt spinning machine is 295°C;
[0098] The crude composite PET fiber and 0.3 mol / L hydrochloric acid solution were added to a beaker at a dosage ratio of 1 g:10 mL to keep them completely immersed. The temperature of the beaker was raised to 80°C and kept warm for 3 hours. The temperature of the beaker was lowered to room temperature and filtered. The filter cake was washed with purified water until it was neutral and then dried. The filter cake was transferred to an oven at 70°C and dried to constant weight to obtain a composite PET fiber.
[0099] S3. Preparation of moisture-absorbing and sweat-proof fabric blanks
[0100] The composite PET fibers were twisted and plied to prepare a mixed yarn with a linear density of 82 dtex, which was then plain woven to obtain a moisture-absorbing and sweat-proof fabric blank with a warp density of 170 yarns / inch and a weft density of 130 yarns / inch.
[0101] S4. Preparation of antibacterial moisture absorbing finishing agent
[0102] Weigh: 134.4 g of 1,3-propane sultone and 403.2 mL of tetrahydrofuran, mix well to obtain a 1,3-propane sultone solution for later use;
[0103] Weigh: 85.2 g of dimethylallylamine and 426 mL of tetrahydrofuran are added to a four-necked flask protected by nitrogen and stirred. The temperature of the four-necked flask is raised to 60° C. The 1,3-propane sultone solution prepared above is added dropwise to the four-necked flask. After the addition is complete, the mixture is kept warm for 7 h and the solvent is evaporated under reduced pressure to obtain modified allylamine;
[0104] Potassium persulfate and deionized water were mixed evenly at a ratio of 1 g:5 mL to obtain an initiator solution;
[0105] Weigh: 100 g of modified allylamine, 40 g of fumaric acid and 600 mL of deionized water are added to a four-necked flask protected by nitrogen and stirred. The temperature of the four-necked flask is raised to 85°C. 30 g of the initiator solution is added dropwise to the four-necked flask. The mixture is kept warm for 8 hours. The solvent is evaporated under reduced pressure. 300 mL of tetrahydrofuran is added to the four-necked flask and stirred until the system is dissolved. 3000 mL of cyclohexane is added to the four-necked flask and stirred for 20 minutes. The filter cake is washed twice with cyclohexane and then dried. The filter cake is transferred to a drying oven at 60°C and vacuum dried to constant weight to obtain a composite polyallylamine.
[0106] Weigh: 100 g of composite polyallylamine and 500 mL of deionized water are added to a beaker and stirred until the system is dissolved, 5 g of sodium hypophosphite monohydrate is added to the beaker and stirred until the system is dissolved, and hydrochloric acid is added to the beaker to adjust the pH of the system to 5 to obtain an antibacterial hygroscopic finishing agent.
[0107] S5. Preparation of moisture-absorbing and sweat-proof fabric
[0108] According to the bath ratio of 1g:35mL, the hygroscopic and sweat-proof fabric blank is immersed in the antibacterial hygroscopic finishing agent at a temperature of 60°C, and the temperature is kept for 80 minutes, and then the hygroscopic and sweat-proof fabric blank is taken out from the antibacterial finishing agent, and drained to obtain a wet fabric with a water content of 65wt%;
[0109] The wet fabric was placed in an oven at 80°C and baked for 10 minutes. The oven temperature was increased to 180°C at a heating rate of 5°C / min, and the fabric was kept warm and baked for 5 minutes. The fabric was naturally cooled to room temperature, washed three times with drinking water, and dried to obtain a moisture-absorbing and sweat-proof fabric.
[0110] Comparative Example 1
[0111] The difference between this comparative example and Example 1 is that in step S1, polyethylene glycol 400 is not added.
[0112] Comparative Example 2
[0113] The difference between this comparative example and Example 1 is that in step S2, the inorganic filler is nano titanium dioxide.
[0114] Comparative Example 3
[0115] The difference between this comparative example and Example 1 is that in step S4, sodium hypophosphite monohydrate is not added.
[0116] Comparative Example 4
[0117] The difference between this comparative example and Example 1 is that step S4 and step S5 are eliminated, and the moisture-absorbing and sweat-proof fabric blank in step S3 is used as the moisture-absorbing and sweat-proof fabric in step S5.
[0118] Performance Testing:
[0119] The wetting time, water absorption rate and maximum wetting radius of the moisture-absorbing and sweat-proof fabric samples prepared in Examples 1-3 and Comparative Examples 1-4 were measured with reference to the standard GB / T 21655.2-2019 “Evaluation of Moisture Absorption and Quick-Drying Properties of Textiles Part 2: Dynamic Moisture Transfer Method”;
[0120] The antibacterial rates of the moisture-absorbing and anti-perspiration fabric samples prepared in Examples 1-3 and Comparative Examples 1-4 against Escherichia coli, Staphylococcus aureus and Candida albicans were measured with reference to the standard GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method";
[0121] After washing the moisture-absorbing and sweat-proof fabric samples prepared in Examples 1-3 and Comparative Examples 1-4 20 times with household laundry detergent, the moisture-absorbing and quick-drying properties and antibacterial properties of the samples were re-measured according to the above standards. The specific test results are shown in Tables 1 and 2.
[0122] Table 1-Test data of moisture absorption and quick-drying performance of samples
[0123]
[0124] Table 2- Antibacterial performance test data of samples
[0125]
[0126] Data Analysis:
[0127] Comparing and analyzing the data in Table 1 and Table 2, the soaking time of the moisture-absorbing and sweat-proof fabric prepared by the present invention is reduced to 2.81s, the retention rate after washing reaches 95.37%, the water absorption rate reaches 78.8% / s, the retention rate after washing reaches 98.98%, the maximum soaking radius reaches 22.8mm, the retention rate after washing reaches 95.18%, the antibacterial rate against Escherichia coli reaches 97.8%, the retention rate after washing reaches 98.47%, the antibacterial rate against Staphylococcus aureus reaches 98.58%, the retention rate after washing reaches 95.37%, the antibacterial rate against Candida albicans reaches 97.1%, and the retention rate after washing reaches 99.28%, and all performance data are better than those of the comparative example;
[0128] It is explained that the present invention strengthens and modifies polyethylene terephthalate by modified PET and inorganic fillers to prepare porous hydrophilic composite PET fibers, which are prepared into fabrics and then impregnated with antibacterial moisture-absorbing finishing agents, which not only effectively improves the moisture absorption and quick-drying properties of the moisture-absorbing and sweat-proof fabrics, prevents sweat from fermenting on the fabrics to produce odor, but also improves their water-washing resistance.
[0129] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a moisture-absorbing and sweat-proof fabric, characterized in that: The following steps are involved: S1, polyethylene terephthalate, modified PET, inorganic filler and additive are mixed evenly and added into a twin-screw extruder, melt-extruded into a melt spinning machine, and melt-spinned to obtain a composite PET fiber crude product; S2, adding the crude composite PET fiber and the hydrochloric acid solution into a beaker to keep them completely immersed, raising the temperature of the beaker to 70-80° C., and heat-treating for 2-3 hours, and post-treating to obtain the composite PET fiber; S3, plying and twisting the composite PET fibers to prepare a mixed yarn with a linear density of 77-82 dtex, and then preparing a moisture-absorbing and sweat-proof fabric blank by weaving a plain weave; S4. Using an antibacterial moisture-absorbing finishing agent to perform padding finishing on the moisture-absorbing and sweat-proof fabric blank to obtain the moisture-absorbing and sweat-proof fabric.
2. The method for preparing a moisture-absorbing and sweat-proof fabric according to claim 1, characterized in that: In step S1, the weight ratio of the polyethylene terephthalate, the modified PET, the inorganic filler and the additive is 80-100:55-65:1.5-2:0.8-1, the additive is composed of a dispersant, a plasticizer and an antioxidant in a weight ratio of 2:3:1, and the inorganic filler is composed of nano titanium dioxide and zinc chloride in a weight ratio of 1:1; in step S2, the amount ratio of the composite PET fiber crude product and the hydrochloric acid solution is 1g:10mL, and the concentration of the hydrochloric acid solution is 0.1-0.3mol / L; in step S3, the warp density of the moisture-absorbing and sweat-proof fabric blank is 140-170 strands / inch, and the weft density is 90-130 strands / inch.
3. The method for preparing a moisture-absorbing and sweat-proof fabric according to claim 1, characterized in that: Modified PET is processed by the following steps: A1. Add sodium 5-sulfoisophthalate dimethyl ester, ethylene glycol and a catalyst into a four-necked flask and stir. The temperature of the four-necked flask is raised to 190-200° C. and stirred for 6-8 hours. After post-treatment, sodium 5-sulfoisophthalate diethylene glycol ester is obtained. A2. Add dihydroxyethyl terephthalate, sodium diethylene glycol 5-sulfonate isophthalate, terephthalic acid, polyethylene glycol 400, ethylene glycol and a catalyst into a nitrogen-protected four-necked flask and stir. The temperature of the four-necked flask is raised to 240-260° C., the pressure of the four-necked flask is reduced to 80-100 Pa, and the reaction is kept warm for 5-7 hours. The modified PET is obtained by post-treatment.
4. The method for preparing a moisture-absorbing and sweat-proof fabric according to claim 3, characterized in that: In step A1, the weight ratio of dimethyl 5-sulfonate sodium isophthalate, ethylene glycol and the catalyst is 3:1:0.01; in step A2, the weight ratio of bis(hydroxyethyl) terephthalate, dimethyl 5-sulfonate sodium isophthalate, terephthalic acid, polyethylene glycol 400, ethylene glycol 62.1 and the catalyst is 25:29:33:40:20:1, and the catalyst is zinc acetate.
5. The method for preparing a moisture-absorbing and sweat-proof fabric according to claim 1, characterized in that: The antibacterial hygroscopic finishing agent is processed by the following steps: B1, adding modified allylamine, fumaric acid and deionized water into a four-necked flask protected by nitrogen and stirring, raising the temperature of the four-necked flask to 75-85°C, dropping the initiator solution into the four-necked flask, keeping the temperature for reaction for 6-8h, and post-treating to obtain composite polyallylamine; B2. Add the composite polyallylamine and deionized water into a beaker and stir until the system is dissolved. Add the catalyst into the beaker and stir until the system is dissolved. Stir for 10-20 minutes and adjust the pH of the system to 4-5 to obtain an antibacterial hygroscopic finishing agent.
6. The method for preparing a moisture-absorbing and sweat-proof fabric according to claim 5, characterized in that: In step B1, the modified allylamine, fumaric acid, deionized water and initiator solution are used in a ratio of 5g:2g:30mL:1.5g, and the initiator solution is composed of potassium persulfate and deionized water in a ratio of 1g:5mL; in step B2, the composite polyallylamine, deionized water and catalyst are used in a ratio of 10g:40-50mL:0.3-0.5g, and the catalyst is sodium hypophosphite monohydrate.
7. The method for preparing a moisture-absorbing and sweat-proof fabric according to claim 5, characterized in that: The preparation method of the modified allylamine comprises the following steps: adding dimethylallylamine and tetrahydrofuran into a four-necked flask protected by nitrogen and stirring, raising the temperature of the four-necked flask to 50-60°C, dripping a 1,3-propane sultone solution into the four-necked flask, and keeping the temperature for reaction for 6-7h after the dripping is completed, and post-treating to obtain the modified allylamine, wherein the usage ratio of the dimethylallylamine and the 1,3-propane sultone is 1 mol:1.1 mol.
8. The method for preparing a moisture-absorbing and sweat-proof fabric according to claim 1, characterized in that: In step S4, the padding finishing method is: immersing the hygroscopic and sweat-proof fabric blank into an antibacterial hygroscopic finishing agent at a temperature of 50-60° C., keeping warm and soaking for 60-80 minutes, taking the hygroscopic and sweat-proof fabric blank out of the antibacterial finishing agent, draining, obtaining a wet fabric with a water content of 55-65wt%, baking and drying, and obtaining a hygroscopic and sweat-proof fabric.
9. The method for preparing a moisture-absorbing and sweat-proof fabric according to claim 8, characterized in that: The bath ratio of the moisture-absorbing and sweat-proof fabric blank and the antibacterial moisture-absorbing finishing agent is 1g:25-35mL, and the baking and drying operation comprises: placing the wet fabric in an oven at a temperature of 70-80°C, baking for 8-10min, increasing the oven temperature to 160-180°C at a heating rate of 3-5°C / min, baking at a heat preservation rate of 3-5°C / min for 3-5min, naturally cooling to room temperature, washing with drinking water for 3 times, and drying to obtain the moisture-absorbing and sweat-proof fabric.
10. A moisture-absorbing and sweat-proof fabric, characterized in that: The moisture-absorbing and sweat-proof fabric is obtained by using the preparation method of the moisture-absorbing and sweat-proof fabric as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Novel sweat stain prevention fabric
CN114059218A